Assessment of cost of innovation versus the value of health gains associated with treatment of chronic hepatitis C in the United States: The quality-adjusted cost of care. Issue 41 (October 2016) - Younossi, Zobair M.; Park, Haesuk; Dieterich, Douglas; Saab, Sammy; Ahmed, Aijaz; Gordon, Stuart C.
Abstract : Supplemental Digital Content is available in the text Abstract: Background: New direct-acting antiviral (DAA) therapy has dramatically increased cure rates for patients infected with hepatitis C virus (HCV), but has also substantially raised treatment costs. Aim: The aim of this analysis was to evaluate the therapeutic benefit and net costs (i.e. efficiency frontier) and the quality-adjusted cost of care associated with the evolution of treatment regimens for patients with HCV genotype 1 in the United States. Design: A decision-analytic Markov model. Data source: Published literature and clinical trial data. Time horizon: Life Time. Perspective: Third-party payer. Intervention: This study compared four approved regimens in treatment-naïve genotype 1 chronic hepatitis C patients, including pegylated interferon and ribavirin (PR), first generation triple therapy (boceprevir + PR and telaprevir + PR), second generation triple therapy (sofosbuvir + PR and simeprevir + PR) and all-oral DAA regimens (ledipasvir/sofosbuvir and ombitasvir + paritaprevir/ritonavir + dasabuvir ± ribavirin). Outcome measure: Quality-adjusted cost of care (QACC). QACC was defined as the increase in treatment cost minus the increase in the patient's quality-adjusted life years (QALYs) when valued at $50, 000 per QALY. Results: All-oral therapy improved the average sustained virologic response (SVR) rate to 96%, thereby offsetting the high drug acquisition cost of $85, 714, which resulted in the highest benefit based on the efficiency frontier. Furthermore, while oral therapies increased HCV drug costs by $48, 350, associated QALY gains decreased quality-adjusted cost of care by $14, 120 compared to dual therapy. When the value of a QALY was varied from $100, 000 to $300, 000, the quality adjusted cost of care compared to dual therapy ranged from − $21, 234 to − $107, 861, − $89, 007 to − $293, 130, − $176, 280 to − $500, 599 for first generation triple, second generation triple, and all-oral therapies, respectively. Primary efficacy and safety measurements for drug regimens were sourced from clinical trials data rather than a real-world setting. Factors such as individual demographic characteristics, comorbidities and alcohol consumption of the individual patients treated may alter disease progression but were not captured in this analysis. Conclusion: New DAA treatments provide short-term and long-term clinical and economic value to society. Primary funding source: Gilead Sciences, Inc.